Iridium-catalyzed hydroacylation reactions of C1-substituted oxabenzonorbornadienes with salicylaldehyde: an experimental and computational study - Ho, Angel; Pounder, Austin; Valluru, Krish; Chen, Leanne D.; Tam, William (Beilstein Journal of Organic Chemistry, 2022)
An experimental and theoretical investigation on the iridium-catalyzed hydroacylation of C1-substituted oxabenzonorbornadienes with salicylaldehyde is reported. Utilizing commercially available [Ir(COD)Cl]2 in the presence of 5 M KOH in dioxane at 65 °C, provided a variety of hydroacylated bicyclic adducts in up to a 95% yield with complete stereo- and regioselectivity. The mechanism and origins of selectivity in the iridium-catalyzed hydroacylation reaction has been examined at the M06/Def2TZVP level of theory. The catalytic cycle consists of three key steps including oxidative addition into the aldehyde C–H bond, insertion of the olefin into the iridium hydride, and C–C bond-forming reductive elimination. Computational results indicate the origin of regioselectivity is involved in the reductive elimination step.
Keywords: C–H activation; density functional theory; hydroacylation; iridium catalysis; regioselectivity

(untitled) - Nicolaou, K. C. (Proc. R. Soc. A, 2014)

(untitled) - Negishi, E.-i. (Angew. Chem., Int. Ed., 2011)

(untitled) - Ruiz-Castillo, P.; Buchwald, S. L. (Chem. Rev., 2016)

(untitled) - Suzuki, A. (Angew. Chem., Int. Ed., 2011)

(untitled) - Biffis, A.; Centomo, P.; Del Zotto, A.; Zecca, M. (Chem. Rev., 2018)

(untitled) - Kundu, K.; McCullagh, J. V.; Morehead, A. T. (J. Am. Chem. Soc., 2005)

(untitled) - Colby, D. A.; Bergman, R. G.; Ellman, J. A. (Chem. Rev., 2010)

(untitled) - Leung, J. C.; Krische, M. J. (Chem. Sci., 2012)

(untitled) - Willis, M. C. (Chem. Rev., 2010)

(untitled) - Newton, C. G.; Wang, S.-G.; Oliveira, C. C.; Cramer, N. (Chem. Rev., 2017)

(untitled) - Zeng, X. (Chem. Rev., 2013)

(untitled) - Yang, L.; Huang, H. (Chem. Rev., 2015)

(untitled) - Murphy, S. K.; Dong, V. M. (Chem. Commun., 2014)

(untitled) - Rayabarapu, D. K.; Cheng, C.-H. (Acc. Chem. Res., 2007)

(untitled) - Lautens, M.; Fagnou, K.; Hiebert, S. (Acc. Chem. Res., 2003)

(untitled) - Boutin, R.; Koh, S.; Tam, W. (Curr. Org. Synth., 2019)

(untitled) - Vivek Kumar, S.; Yen, A.; Lautens, M.; Guiry, P. J. (Chem. Soc. Rev., 2021)

(untitled) - Villeneuve, K.; Riddell, N.; Jordan, R. W.; Tsui, G. C.; Tam, W. (Org. Lett., 2004)

(untitled) - Riddell, N.; Tam, W. (J. Org. Chem., 2006)

(untitled) - Villeneuve, K.; Riddell, N.; Tam, W. (Tetrahedron, 2006)

(untitled) - Qin, H.; Chen, J.; Li, K.; He, Z.; Zhou, Y.; Fan, B. (Chem. – Asian J., 2018)

(untitled) - Yang, Q.; Yu, L.; Xu, J.; Li, S.; Liu, S.; Chen, H.; Zhou, Y.; Wang, L.; Fan, B. (Tetrahedron: Asymmetry, 2014)

(untitled) - Chao, K. C.; Rayabarapu, D. K.; Wang, C.-C.; Cheng, C.-H. (J. Org. Chem., 2001)

(untitled) - Shih, H.-T.; Shih, H.-H.; Cheng, C.-H. (Org. Lett., 2001)

(untitled) - Jack, K.; Tam, W. (J. Org. Chem., 2013)

(untitled) - Huang, D.-J.; Cheng, C.-H. (J. Organomet. Chem., 1995)

(untitled) - Nishimura, T.; Kawamoto, T.; Sasaki, K.; Tsurumaki, E.; Hayashi, T. (J. Am. Chem. Soc., 2007)

(untitled) - Ballantine, M.; Menard, M. L.; Tam, W. (J. Org. Chem., 2009)

(untitled) - Yen, A.; Choo, K.-L.; Yazdi, S. K.; Franke, P. T.; Webster, R.; Franzoni, I.; Loh, C. C. J.; Poblador-Bahamonde, A. I.; Lautens, M. (Angew. Chem., 2017)

(untitled) - Villeneuve, K.; Tam, W. (J. Am. Chem. Soc., 2006)

(untitled) - Peng, F.; Fan, B.; Shao, Z.; Pu, X.; Li, P.; Zhang, H. (Synthesis, 2008)

(untitled) - Yang, J.; Sekiguchi, Y.; Yoshikai, N. (ACS Catal., 2019)

(untitled) - Sawano, T.; Ou, K.; Nishimura, T.; Hayashi, T. (Chem. Commun., 2012)

(untitled) - Chen, W.; Yang, W.; Wu, R.; Yang, D. (Green Chem., 2018)

(untitled) - Lin, Q.; Yang, W.; Yao, Y.; Chen, S.; Tan, Y.; Chen, D.; Yang, D. (Org. Lett., 2019)

(untitled) - Sakae, R.; Hirano, K.; Satoh, T.; Miura, M. (Angew. Chem., Int. Ed., 2015)

(untitled) - Lee, H.; Lee, B. Y.; Yun, J. (Org. Lett., 2015)

(untitled) - Prakash, S.; Chang, Y.-C.; Cheng, C.-H. (Chem. – Asian J., 2018)

(untitled) - Koh, S.; Pounder, A.; Brown, E.; Tam, W. (Eur. J. Org. Chem., 2020)

(untitled) - Koh, S.; Pounder, A.; Brown, E.; Tam, W. (Org. Lett., 2020)

(untitled) - Cheng, H.; Yang, D. (J. Org. Chem., 2012)

(untitled) - Yang, X.; Yang, W.; Yao, Y.; Deng, Y.; Yang, D. (Org. Chem. Front., 2019)

(untitled) - Long, Y.; Li, X.; Pan, X.; Ding, D.; Xu, X.; Zuo, X.; Yang, D.; Wang, S.; Li, C. (Catal. Lett., 2014)

(untitled) - Yang, D.; Long, Y.; Zhang, J.; Zeng, H.; Wang, S.; Li, C. (Organometallics, 2010)

(untitled) - Chen, J.; Zou, L.; Zeng, C.; Zhou, Y.; Fan, B. (Org. Lett., 2018)

(untitled) - Jack, K.; Fatila, E.; Hillis, C.; Tam, W. (Synth. Commun., 2013)

(untitled) - Li, L.-P.; Rayabarapu, D. K.; Nandi, M.; Cheng, C.-H. (Org. Lett., 2003)

(untitled) - Tan, Y.; Yao, Y.; Yang, W.; Lin, Q.; Huang, G.; Tan, M.; Chen, S.; Chen, D.; Yang, D. (Adv. Synth. Catal., 2020)

(untitled) - Shen, G.; Khan, R.; Yang, F.; Yang, Y.; Pu, D.; Gao, Y.; Zhan, Y.; Luo, Y.; Fan, B. (Asian J. Org. Chem., 2019)

(untitled) - Li, Y.; Yang, W.; Cheng, G.; Yang, D. (J. Org. Chem., 2016)

(untitled) - Millet, R.; Gremaud, L.; Bernardez, T.; Palais, L.; Alexakis, A. (Synthesis, 2009)

(untitled) - Yang, D.; Liang, N. (Org. Biomol. Chem., 2014)

(untitled) - Yang, D.; Hu, P.; Long, Y.; Wu, Y.; Zeng, H.; Wang, H.; Zuo, X. (Beilstein J. Org. Chem., 2009)

(untitled) - Lautens, M. (Synlett, 1993)

(untitled) - Fleming, M. J.; McManus, H. A.; Rudolph, A.; Chan, W. H.; Ruiz, J.; Dockendorff, C.; Lautens, M. (Chem. – Eur. J., 2008)

(untitled) - Lautens, M.; Rovis, T. (Tetrahedron, 1999)

(untitled) - Madan, S.; Cheng, C.-H. (J. Org. Chem., 2006)

(untitled) - Pounder, A.; Ho, A.; Macleod, M.; Tam, W. (Curr. Org. Synth., 2021)

(untitled) - Allen, A.; Le Marquand, P.; Burton, R.; Villeneuve, K.; Tam, W. (J. Org. Chem., 2007)

(untitled) - Deng, Y.; Yang, W.; Yao, Y.; Yang, X.; Zuo, X.; Yang, D. (Org. Biomol. Chem., 2019)

(untitled) - Hill, J.; Wicks, C.; Pounder, A.; Tam, W. (Tetrahedron Lett., 2019)

(untitled) - Edmunds, M.; Menard, M. L.; Tam, W. (Synth. Commun., 2015)

(untitled) - Pounder, A.; Bishop, F.; Chen, L. D.; Tam, W. (Eur. J. Org. Chem., 2021)

(untitled) - Nagamoto, M.; Nishimura, T. (Chem. Commun., 2015)

(untitled) - Tanaka, K.; Tanaka, M.; Suemune, H. (Tetrahedron Lett., 2005)

(untitled) - Stemmler, R. T.; Bolm, C. (Adv. Synth. Catal., 2007)

(untitled) - Lough, A. J.; Ho, A.; Tam, W. (IUCrData, 2020)

Gaussian 16, Revision C.01 (Gaussian, Inc., 2016)

(untitled) - Zhao, Y.; Truhlar, D. G. (Theor. Chem. Acc., 2008)

(untitled) - Weigend, F.; Ahlrichs, R. (Phys. Chem. Chem. Phys., 2005)

(untitled) - Grimme, S.; Antony, J.; Ehrlich, S.; Krieg, H. (J. Chem. Phys., 2010)

(untitled) - Miertuš, S.; Scrocco, E.; Tomasi, J. (Chem. Phys., 1981)

CYLview, 1.0b (Université de Sherbrooke, 2009)

(untitled) - Hyatt, I. F. D.; Anderson, H. K.; Morehead, A. T., Jr; Sargent, A. L. (Organometallics, 2008)

(untitled) - von Delius, M.; Le, C. M.; Dong, V. M. (J. Am. Chem. Soc., 2012)

(untitled) - Wang, M.; Zhang, X.; Chen, Z.; Tang, Y.; Lei, M. (Sci. China: Chem., 2014)

(untitled) - Chaplin, A. B.; Hooper, J. F.; Weller, A. S.; Willis, M. C. (J. Am. Chem. Soc., 2012)

(untitled) - Pawley, R. J.; Huertos, M. A.; Lloyd-Jones, G. C.; Weller, A. S.; Willis, M. C. (Organometallics, 2012)